EXPLORING TRANSLANGUAGING AND INDEXICALITY IN SIXTH-SEMESTER ENGLISH STUDENTS'SEMINAR PERFORMANCES: AN ANTHROPOLINGUISTICS STUDY - Octavianna, Yessy octavianna; Sipayung, Kammer; Tambunan, Agnes Tiomadina; Naibaho, Yohana Friscila (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2024)
The purpose of this study is to find out 1) the types of use of translanguaging and indexicality on students’ performance in the Seminar on ELT course and 2) the impact of the use of translanguaging in teaching Seminar on ELT courses in honing student performance. This study observed using an anthropolinguistic approach using analytical parameters, namely interconnection, valuability, and sustainability. A qualitative paradigm with an ethnographic model used in this study by applying twelve steps both in interview and observation methods. Translanguaging is a phenomenon of language use in which people use two or more languages simultaneously. This translanguaging often occurs in teaching when lecturers teach in class or when students present their journals or papers in front of participants in the class. This translanguaging carried out by students requires a language performance style carried out by students in front of all participants present to show their ability and expertise in expressing ideas orally. Translanguaging and indexicality use in students’ performance when presenting their journals or papers. Indexicality or Index can be in lingual form or Non lingual form. A speaker can index changes in relevant aspects of his/her identity in a conversational context. Translanguaging requires innovative language creativity in conveying thinking ideas. The use and application of this trans language can be seen from the performance style of students in front of the class when presenting their papers or journals.